2016
DOI: 10.1007/s10461-016-1338-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Associated with Resilience in a National Community-Based Cohort of Australian Gay Men Living with HIV

Abstract: HIV-positive gay men may experience multiple sources of adversity and stress, related both to their HIV diagnosis and sexual identity. Most of these men, however, do not experience mental health problems. Little is known about factors that help them achieve resilience in the face of life challenges. This study examined psychosocial factors associated with resilience in a national community-based sample of 357 Australian HIV-positive gay men. Resilience was measured using the Connor-Davidson Resilience Scale. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 41 publications
2
23
0
1
Order By: Relevance
“…Social support and community engagement both contributed independently to resilience and mastery. Multiple studies examining adults living with HIV have found social support and other positive social appraisals to be associated both qualitatively and quantitatively with resilience and mastery (De Santis et al, 2013;Emlet et al, 2010Emlet et al, , 2013Fang et al, 2015;Lyons et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support and community engagement both contributed independently to resilience and mastery. Multiple studies examining adults living with HIV have found social support and other positive social appraisals to be associated both qualitatively and quantitatively with resilience and mastery (De Santis et al, 2013;Emlet et al, 2010Emlet et al, , 2013Fang et al, 2015;Lyons et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Smith and Hayslip (2012) suggest that intrapersonal, interpersonal, and environmental (including community) resources can contribute to resilience. However, the number of empirical papers that examine resilience in adults of any age living with HIV remains limited (De Santis, 2008;De Santis, Florom-Smith, Vermeesch, Barroso, & DeLeon, 2013;Fang et al, 2015;Lyons, Haywood, & Rozbroj, 2016). There are, however, emerging consistencies across studies that focus on resilience among people living with HIV.…”
Section: Resiliencementioning
confidence: 99%
“…We specifically focused on psychosocial variables related to stigma, discrimination, and social support. A focus on stigma and discrimination was included because previous studies have shown that stigma, whether related to HIV or sexuality, can have a powerful impact on the lives of HIV-positive gay men [ 24 , 29 ]. A focus on social support was included because the provision of support is often a major focus of HIV organizations, governments, and health agencies.…”
Section: Methodsmentioning
confidence: 99%
“…More recent studies have found optimism to be associated with greater psychological well-being and reductions in perceived HIV-related stigma among PLHIV referred for mental health services within a HIV clinic [ 22 ], while dispositional optimism and perceived confidence in one’s ability to achieve a favorable outcome were found to predict increases in positive affect over a 2-month period among participants recruited from a HIV outpatient clinic [ 23 ]. Some studies have also examined resilience among HIV-positive gay men [ 24 ], such as hardiness [ 25 ] and coping with life challenges [ 26 ]. Although resilience is an aspect of flourishing, having resilience does not necessarily mean a person is flourishing [ 12 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…better mental health). On the other hand, factors such as past adverse life events (Brewin, Andrews, & Valentine, 2000;Butler, Koopman, Classen, & Spiegel, 1999), sex (Ginzburg & Ein-Dor, 2011;Moergeli, Wittmann, & Schnyder, 2012;Zhu et al, 2014), age (Havik, 1990;Moergeli et al, 2012), income (Lyons, Heywood, & Rozbroj, 2016), civil status (Havik, 1990;Moergeli et al, 2012;Morris, Yelin, Panopalis, Julian, & Katz, 2011), or education (Morris et al, 2011;Van Leeuwen et al, 2012), have been inconsistently associated to psychological adaptation following CHC. Using a sample with different types of CHCs could lead to the identification of the most important factors that are related to psychological adaptation to physical CHC overall.…”
Section: Psychological Distress Trajectories In Chronic Physical Healmentioning
confidence: 99%